Use of Library for Promoting Students’ Learning - Sigdel, Surya; Sharma, Mani Ram (International Journal of Educational Review, 2023)
Library practices in schools exert significant influence on students’ learning attitude and behavior. This paper explores the existing situation of library practices in community and institutional schools of Nepal. Despite a number of options to educate students in school from library-use, library provision and its existing practices in community and institutional schools in Nepal are still unsearched. In context students study only during the time of their class, assignment and examination preparation, how the schools make use of library for the promotion of students’ learning is the main concern of the study. Information for the study was collected from fieldnotes and lived experiences of eight participants: one teacher and one student from each of four schools: two institutional and two community. The study found that teachers in community schools occasionally visit the library and rarely encourage their students to benefit from the library. However, some students were found to borrow books from the library. As students in institutional schools have library period once a week, they enjoy reading books or doing something in the library. Overall library practice in Nepal lacks adequate proficiency in management, administration, and provision of study materials; and ultimately has not motivated students’ hearty participation.